2000
DOI: 10.1017/s0025315400003039
|View full text |Cite
|
Sign up to set email alerts
|

The structure and taxonomic composition of sublittoral meiofauna assemblages as an indicator of the status of marine environments

Abstract: A study was conducted between 1997 and 1999 to investigate meiofauna assemblages from selected inshore and offshore locations around the UK coast. The main objective was to relate the differences in meiofauna distribution patterns to a number of measured environmental variables and to establish more clearly the sensitivity of meiofauna communities to anthropogenic disturbance. Results from univariate and multivariate data analyses show that distinct spatial differences in species distribution patterns exist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 16 publications
2
47
0
3
Order By: Relevance
“…Oberbeckmann et al [12] suggested that microplastics could carry pathogens encountered in the feces of marine organisms, and transport of human fecal bacteria on plastics has also been discussed [13]. There is a particular requirement to determine how this debris affects organisms at low trophic levels, such as invertebrates used for biomonitoring purposes [79,80]. Impacts of plastisphere assemblages on processes such as nutrient cycling and primary production should also be investigated.…”
Section: Interactions With Higher Organisms and The Wider Environmentmentioning
confidence: 99%
“…Oberbeckmann et al [12] suggested that microplastics could carry pathogens encountered in the feces of marine organisms, and transport of human fecal bacteria on plastics has also been discussed [13]. There is a particular requirement to determine how this debris affects organisms at low trophic levels, such as invertebrates used for biomonitoring purposes [79,80]. Impacts of plastisphere assemblages on processes such as nutrient cycling and primary production should also be investigated.…”
Section: Interactions With Higher Organisms and The Wider Environmentmentioning
confidence: 99%
“…These characteristics make meiofaunal organisms excellent candidates to test general ecological hypotheses and theories (Jessup et al 2004;Nascimento et al 2011Nascimento et al , 2012Bonaglia et al 2014). However, this group represents an often neglected component of marine biodiversity (Curini-Galletti et al 2012) and is generally poorly studied (particularly in the deep sea) because most applied programmes target the larger macrofauna, which are more readily identifiable and countable than meiofauna (Schratzberger et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in meiofauna abundance has already been qualitatively related to organic input (SCHRATZBERGER et al, 2000;DALTO et al, 2006) and to sediment redox potential (LAMPADARIOU et al, 2005). Widbom and Elmgren (1988) observed that only some meiofauna groups presented a positive response to an increase in organic input.…”
Section: Discussionmentioning
confidence: 93%